Проблеми та перспективи експорту аграрної продукції України - Лисак, Оксана Іванівна; Лысак, Оксана Ивановна; Lysak, Oksana; Андрєєва, Лариса Олександрівна; Андреева, Лариса Александровна; Andrieieva, Larysa (My University, 2017)
UK: У статті розглянуто проблеми збуту сільськогосподарської продукції аграрними підприємствами. Проаналізовано канали збуту аграрної продукції в Україні. Визначено переваги й вади реалізації сільськогосподарської продукції в рамках Угоди про асоціацію з Європейським Союзом. Розглянуто сучасні тенденції в експорті української аграрної продукції з урахуванням переорієнтації на азійські та європейські ринки. RU: В статье рассмотрены проблемы сбыта сельскохозяйственной продукции аграрными предприятиями. Проанализированы каналы сбыта аграрной продукции в Украине. Определены преимущества и недостатки реализации сельскохозяйственной продукции в рамках Соглашения об ассоциации с Европейским Союзом. Рассмотрены современные тенденции в экспорте украинской аграрной продукции с учетом переориентации на азиатские и европейские рынки. EN: The aim of this publication is to review current trends Ukrainian exports of agricultural products and develop recommendations on the prospects of export of agricultural products in Ukraine. The problem of marketing of agricultural products by agricultural enterprises is considered in the article. The distribution channels of agricultural products in Ukraine are analyzed. The factors constraining agricultural exports are established. Advantages and disadvantages of agricultural products within the Association Agreement with the European Union are analyzed. Analyzed the first results of cooperation with the EU in agriculture. The problems of the use of quotas dispose of agricultural products within the Association Agreement with the European Union are identified. An simplified legalization exports from Ukraine to the EU of animal origin products is offered. The export of agricultural products to other countries is analyzes. The modern trend in the export of Ukrainian agricultural products based on the reorientation of Asian and European markets is considered. The strategic directions of development of Ukrainian agricultural exports are identified.
Проблемы и перспективы экспорта аграрной продукции Украины
Problems and prospects of Ukraine’s export of agricultural products
Keywords: аграрна продукція; збут; реалізація сільськогосподарської продукції; Угода про асоціацію з Європейським Союзом; квоти на поставку продукції; експорт аграрної продукції; аграрная продукция; сбыт; реализация сельскохозяйственной продукции; Соглашение об ассоциации с Европейским Союзом; квоты на поставку продукции; экспорт аграрной продукции; agricultural production; marketing; sale of agricultural products; the Association Agreement with the European Union; quota for the supply of products; the export of agricultural products